α+-Thalassemia protects children against disease caused by other infections as well as malaria - Allen, S; O'Donnell, A; Alexander, N; Alpers, M; Peto, T; Clegg, J; Weatherall, D (1997)
In the South West Pacific region, the striking geographical correlation between the frequency of α+ -thalassemia and the endemicity of Plasmodium falciparum suggests that this hemoglobinopathy provides a selective advantage against malaria. In Vanuatu, paradoxically, α+ -thalassemia increases the incidence of contracting mild malaria in the first 2 years of life, but severe disease was too uncommon to assess adequately. Therefore, we undertook a prospective case-control study of children with severe malaria on the north coast of Papua New Guinea, where malaria transmission is intense and α+ - thalassemia affects more than 90% of the population. Compared with normal children, the risk of having severe malaria was 0.40 (95% confidence interval 0.22-0.74) in α+ -thalassemia homozygotes and 0.66 (0.37-1.20) in heterozygotes. Unexpectedly, the risk of hospital admission with infections other than malaria also was reduced to a similar degree in homozygous (0.36; 95% confidence interval 0.22-0.60) and heterozygous (0.63; 0.38-1.07) children. This clinical study demonstrates that a malaria resistance gene protects against disease caused by infections other than malaria. The mechanism of the remarkable protective effect of α+-thalassemia against severe childhood disease remains unclear but must encompass the clear interaction between this hemoglobinopathy and both malarial and nonmalarial infections.